Mastering leadership : key techniques for managing and leading a winning team - Williams, Michael R. (London : Thorogood, 1998)
This work reveals the key skills needed by any leader, and shows how they can be used in practice. It includes a range of practical features throughout, such as key questions, key checklists, activities, guides to best practice, key learning points and key management concepts.
Includes bibliographical references (p. 258-261).
oif 09/02/15
Loans
Keywords: Industrial management; Leadership